2015
DOI: 10.1080/13102818.2015.1078744
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and optimization ofCandida rugosananobioconjugates catalysed synthesis of methyl oleate by response surface methodology

Abstract: Esters, such as methyl oleate, are functionally important compounds in many industrial sectors, mainly as components for manufacturing of emulsifiers, detergents, intermediate stabilizers and wetting agents. Acid functionalization of multiwalled carbon nanotubes (F-MWCNTs) by using a mixture of HNO 3 and H 2 SO 4 (1:3, v:v) was employed as the matrix for the adsorption of Candida rugosa lipase (CRL) as nanobioconjugates (CRL-MWCNTs) for the production of methyl oleate. Structural information of the developed C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…The coefficient of determination, R 2 , obtained for the model was .9780, explaining 97.80% of the variation in the mass yield of the mixture of castor oil and peanut oil in the production of biodiesel. The high value of the coefficient of determination confirms that the quadratic polynomial model was adequate to explain the relationship between the real response and the independent reaction variables, a similar finding verified in other studies with biodiesel optimization …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The coefficient of determination, R 2 , obtained for the model was .9780, explaining 97.80% of the variation in the mass yield of the mixture of castor oil and peanut oil in the production of biodiesel. The high value of the coefficient of determination confirms that the quadratic polynomial model was adequate to explain the relationship between the real response and the independent reaction variables, a similar finding verified in other studies with biodiesel optimization …”
Section: Resultssupporting
confidence: 83%
“…The high value of the coefficient of determination confirms that the quadratic polynomial model was adequate to explain the relationship between the real response and the independent reaction variables, a similar finding verified in other studies with biodiesel optimization. 27,28 In this work, the model shown all linear terms, alcohol:oil ratio and catalyst amount as quadratic terms were significant. Cubic terms were important to describe significantly the model.…”
Section: Regression Analysismentioning
confidence: 63%
“…The minimum AV can be found in high temperatures 130 and high IL load 10 18 . And elliptical contours can be obtained between temperature with IL load, which indicated that the interaction of reaction temperature and IL load was very significant 24 . Figure 6B shows that, compared with reaction time, the effect of reaction temperature on the synthesis of RA estolides was more significant, which can also be found from Table 2.…”
Section: Model Fittingmentioning
confidence: 93%
“…In addition, Wahab et al, (2014) stated that the protein folds begin to unravel excessively when the optimum temperature of an enzyme has been exceeded. The reason for this kind of behavior is because the molecules (DehSN1 and 2,2DCP) tend to move faster when the temperature is raised, concomitant with the observed increase in rate of the DehSN1 reaction (Marzuki et al, 2015;Manan et al, 2016;Isah et al, 2017;Manan et al, 2018;) between the enzyme and the 2,2DCP molecules within the system. In contrast, the apparent low dehalogenase activity below 30 °C ( Figure 5) was presumably due to the DehSN1 dehalogenase protein structure being too rigid and unable to unfold into its catalytically active form to catalyze the degradation of 2,2DCP (Isah et al, 2017).…”
Section: Characterization Of Dehsn1mentioning
confidence: 99%